Accounting information system effects on job performance: Baghdad University/Iraq - Al-Delfi, Ahmed Faraj Abdulkareem; Khaleel, Moamin Adnan Khaleel (Edelweiss Applied Science and Technology, 2025)
This study examines the effect of accounting information systems (AIS) on job performance at the University of Baghdad, Iraq. The research utilized a quantitative approach represented by a 5-Point Likert scale questionnaire as a tool to collect data reflecting the views of accountants and other non-managerial employees working at this university. To achieve the objectives of the research, internal consistency and normality distribution tests were conducted to ensure the validity and reliability of the data. Simple linear regression and Pearson correlation were used to explain the relationship between AIS and job performance, and an independent sample t-test was also used to test the significance of differences between the two groups of employees mentioned above. The results of the analysis confirm that the data is considered valid and reliable. The t-test found that there are no significant differences in the perceptions of AIS importance in job performance between the two groups. The Pearson correlation indicated that there is a significant positive relationship between accounting information systems and job performance at the p < .01 level. Regression analysis revealed that there is a significant and positive relationship between accounting information systems and job performance.